One-Pot Synthesis of Pyrazine-2-carbaldehyde Containing 1,2,3-Triazoles: In vitro Antibacterial Activity - Podishetty, Srikanth; Ega, Jagadeesh Kumar (Asian Journal of Chemistry, 2026)
In pursuit of enhanced antibacterial agents, a series of 3-(4-(aryl)-1H-1,2,3-triazol-1-yl)pyrazine-2-carbaldehydes was synthesised (4a-k) through the utilisation of 3-aminopyrazine-2-carbaldehyde, alkyne and triflyl azide via an in situ synthesised 3-azidopyrazine-2-carbaldehyde, followed by an assessment of their in vitro antibacterial activity. The investigation of antibacterial efficacy was conducted against three Gram-positive bacterial strains viz. Bacillus subtilis, Staphylococcus aureus and Staphylococcus epidermidis, employing the standard broth microdilution methodology. Among the compounds evaluated, compounds 4f and 4k demonstrated significant antibacterial efficacy, with minimum inhibitory concentration (MIC) values ranging from 3.12 ± 0.39 to 12.5 ± 0.87 µg/mL against the examined Gram-positive bacterial strains. Ultimately, further structural optimization of these potent compounds may lead to their development as promising candidates for future therapeutic applications.